Merger-Driven Listing Dynamics - Eckbo, B. Espen; Lithell, Markus (Journal of Financial and Quantitative Analysis, 2025)
Abstract Stock-market effectiveness in attracting and retaining firms under public ownership depends not only on stand-alone firms’ net listing benefits but also on gains from merging with a public acquirer. Using a novel merger-adjusted listing count, we show that the dramatic (≈50%) post-1996 U.S. listing decline—often attributed to declining listing benefits—is reversed as the “missing” firms de facto continue existing inside their public acquirers. Our merger adjustment also eliminates the U.S. listing gap, pointing instead to a distinct U.S. listing advantage: providing access to a well-functioning market for complex merger transactions.